Analisis Kinerja Pegawai dalam Pelayanan Administrasi Pajak Kendaraan Roda Dua di Samsat Medan Utara - Muhammad Taufiq; Adam Adam; Evi Yunita Kurniaty (Universitas Medan Area, 2022)
The purpose of studiy was to determine employee performance in improwing the quality of two-wheeled motor vehicle tax administration services at the North Medan Samsat office and to determine the inhibiting factor/constraints on employee performance in improwing the quality of two-wheeled motor vehicle tax administration services at the nort medaan samsat office. This study uses a qualitative descriptive method using analysis of performance theory according to Agus Dwiyanto (2006) namaely productivity, service quality, responsiveness, responsibility, accountability. The results of this studiy can be conclouded that the performance of employees in improwingthe quality of taq administration services specifically for two- wheeled motor vehicles at the north medan samsat office has not gone well due to various problems and obstacles faced. Inhibiting factors or obstacles faced are service ti the community is still not optimal, employee discipline is still lacking, human resources are still;ow, internet network. The outhours suggestion in this study is that the Norts Medan Samsat employees carry out health services to the maximum without discriminating between people who take care of taxes and speed up service hours.